Modelo de planejamento da produção com otimização do custo total de atendimento à demanda em uma fábrica de componentes injetados - Ceolin, Bruno Loschi (2018)
The presented master dissertation addresses a production planning problem in a plastic injection molding products company. A mathematical model in Mixed Integer Linear Programming (MILP) is proposed to solve the lot sizing and production sequencing, considering the costs of production, backlogging, and setup. This model was based on the MILP model proposed by Dastidar and Nagi (2005), but a series of parameters and variables were included to better represent the operational conditions. A case study was carried out based on real company data, which involved the set of seven main manufactured parts, which are injected into two machines of 450 tons and one of 380 tons capacity. In addition, computational experiments are conducted to show the model scalability with different parameters. From the implementation and computational resolution of the proposed mathematical model for the practical case, the obtained results show a possibility of reduction in the total time spent with the manufacturing of products, together with a reduction of productive costs.